Penggunaan Alat Dispenser Handsanitizer di Fasilitas Pelayanan Kesehatan Untuk Memutus Mata Rantai Penyebaran COVID-19 Kota Tanjungpinang - Kholilah Samosir; Annisa Pratiwi Putri (Jurnal Salam Sehat Masyarakat (JSSM), 2021)
This corona virus infection also occurred in Indonesia with the number of confirmed cases in 2020 was 162,884. In Riau Islands Province for 2020 the number of confirmed cases is 857 and in Tanjungpinang City itself there are 149 cases with details of 26 active cases, 119 recovered and 4 died. This corona virus can enter the human body through the mucosa of the eyes, nose and mouth when exposed to fluid droplets or granules that come out when we sneeze or cough, either by direct contact with a person carrying the virus or through a surface that that person has touched. The standard recommendation to prevent the spread of infection is through regular hand washing, use of hand sanitizer, apply cough and sneeze etiquette, avoid close contact with anyone showing symptoms of respiratory illness such as coughing and sneezing. One of the places that must be considered in implementing Infection Prevention and Control (PPI) is at the Health Service facility which is visited by many people every day, namely by installing hand sanitizer dispensers in every health service place in Tanjungpinang City.